The Jazz Community as an Art World: A Sociological Perspective - Martin, Peter (Jazz Research Journal, 2005)
Just over forty years ago, the American anthropologists Alan Merriam and Raymond Mack published a paper in which they aimed to present ‘…a factual description of what we shall call the jazz community’ (1960: 211). As they recognised, the term ‘community’ is problematic in various ways, but what Merriam and Mack had in mind was that group of people who not only have an interest in jazz, but who display an ‘…extreme identification with and participation in the occupational role and ideology of the professional jazz musician’ (ibid.) They noted the relatively large proportion of the jazz community who were themselves musicians of some kind, ranging from former professionals to occasional amateurs, and, in part because of this, emphasised the extent to which, from a sociological point of view, professional players and their public could be regarded as members of a single group, sharing a particular ideology (ibid: 217). As more recent research has shown (e.g. DeVeaux, 1995), the high proportion of performers within the jazz public has remained a significant characteristic of the jazz scene generally. For the moment however, I want to focus on the central idea developed by Merriam and Mack. In their words: While the jazz community is characterised by a number of distinctive behavior patterns, almost without exception these tend to cluster around one central theme – the isolation of the group from society at large, an isolation which is at once psychological, social, and physical (ibid).